2014
DOI: 10.1117/1.jbo.19.7.075004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fractional photothermolysis effect in a mouse model using nonlinear optical microscopy

Abstract: Fractional photothermolysis (FP) induces discrete columns of photothermal damage in skin dermis, thereby promoting collagen regeneration. This technique has been widely used for treating wrinkles, sun damage, and scar. In this study, we evaluate the potential of multiphoton microscopy as a noninvasive imaging modality for the monitoring of skin rejuvenation following FP treatment. The dorsal skin of a nude mouse underwent FP treatment in order to induce microthermal zones (MTZs). We evaluated the effect of FP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Due to the collagen non-centrosymmetric molecular structure, it is an effective SHG generator 41 . The images obtained from SHG can be used to provide information on collagen structure within the skin 42 . Guo 43 used SHG to investigate skin rejuvenation after treatment with a 1550 µm fractional laser.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the collagen non-centrosymmetric molecular structure, it is an effective SHG generator 41 . The images obtained from SHG can be used to provide information on collagen structure within the skin 42 . Guo 43 used SHG to investigate skin rejuvenation after treatment with a 1550 µm fractional laser.…”
Section: Discussionmentioning
confidence: 99%
“…The images obtained from SHG can be used to provide information on collagen structure within the skin 42 . Guo 43 used SHG to investigate skin rejuvenation after treatment with a 1550 μm fractional laser. They concluded that it is an appropriate technique to evaluate collagen regeneration by the fractional laser treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation